Multistage information transmission with voluntary monetary transfers - Hitoshi Sadakane (Theoretical Economics, 2023)
We analyze a cheap-talk model in which an informed sender and an uninformed receiver engage in a finite-period communication before the receiver chooses a project. During the communication phase, the sender sends a message in each period, and the receiver then voluntarily pays money for the message. As in the canonical cheap-talk model, all the equilibria are interval partitional; in our setting, however, the set of equilibrium partitions becomes larger. We show that the multistage information transmission with voluntary monetary transfers can improve welfare if the receiver cares more about the decision and the sender cares more about money or if the ex-post sender–receiver incentive conflict over the project choice is small. We derive a multistage information elicitation mechanism without commitment that can be more beneficial to the receiver than a broad class of other communication protocols (e.g., mediation and arbitration).
Keywords: C72; C73; D82; D83; 330; cheap talk; Incomplete information; multistage strategic communication; voluntary monetary transfers